The Effect of Granulocyte Colony Stimulating Factor (G-CSF) on the Outcome of Assisted Reproduction Technology in Thin Endometrium Women: A Meta-Analysis - Li-Jun Lin; Ge Chen; Liang-Zhi Xu; Hui Chen (Clinical and Experimental Obstetrics & Gynecology)
Background: To explore the effect of granulocyte colony-stimulating factor (G-CSF) on thin endometrium in women undergoing assisted reproduction. Methods: We performed a methodical search from their inception to December 2022 in various electronic databases containing PubMed, Cochrane Library, Embase, Web of Science, Scopus, in addition to a manual search. All journals concerning the effect of G-CSF on thin endometrium were found. Selected studies, collected data, and assessed risk of bias were conducted by two investigators under precise inclusion and exclusion criteria independently. We applied Revman 5.3 software to accomplish the Meta-analysis of qualified studies. Results: This research included 8 studies, including 6 randomized controlled trials and 2 non-randomized controlled studies, a total of 673 patients. Based on the meta-analysis, we noted that compared with the control group, G-CSF significant improved embryo implantation rate [risk ratio (RR) =1.91, 95% confidence interval (CI) (1.26, 2.91), p = 0.002] and clinical pregnancy rate [RR = 1.73, 95% CI (1.22, 2.45), p = 0.002]. Compared with the control group, the endometrial thickness in the G-CSF group had non-significant increase compared with that of the control group [mean difference (MD) = 0.81, 95% CI (–0.04, 1.67), p = 0.06], in randomized controlled trial (RCT) studies, subgroup analysis shows G-CSF group increased significantly [MD = 1.13, 95% CI (0.56, 1.67), p< 0.0001]. Conclusions: G-CSF may improve implantation rate and clinical pregnancy rate in assisted reproductive technology, and have the potential to increase the endometrial thickness among women with thin endometrium. However, the results of the included studies should be explained with caution due to their limited quantity and quality, and more studies of higher quality are demanded to prove these findings.